1997
DOI: 10.1136/adc.77.6.526
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in the rate of fall of thyroid stimulating hormone in treated hypothyroidism

Abstract: The rate of fall of serum thyroid stimulating hormone (TSH) concentrations in 32 hypothyroid infants (11 boys, 21 girls) was studied after starting treatment with thyroxine to determine whether it was influenced by initial TSH concentration or the cause of the hypothyroidism. Of 27 patients who had isotope scans before treatment was started, 11 (40%) were athyrotic, 10 (38%) had an ectopic gland, and six (22%) probably had dyshormonogenesis. Treatment was started with thyroxine at 100 µg/m 2 /24 hours at a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…For the children with hypothyroidism, the Japanese Society for Pediatric Endocrinology recommends giving 5 to 7 mg/kg/d at the age of 1 to 5 years [7], hence the dosage applied in our study is less than this recommendation. As for follow-up treatment, Raza et al reported that maintaining serum FT4 levels within the normal range, regardless of TSH concentration, is the safest approach in treating congenital hypothyroidism [8].…”
Section: Discussionmentioning
confidence: 99%
“…For the children with hypothyroidism, the Japanese Society for Pediatric Endocrinology recommends giving 5 to 7 mg/kg/d at the age of 1 to 5 years [7], hence the dosage applied in our study is less than this recommendation. As for follow-up treatment, Raza et al reported that maintaining serum FT4 levels within the normal range, regardless of TSH concentration, is the safest approach in treating congenital hypothyroidism [8].…”
Section: Discussionmentioning
confidence: 99%
“…We do not have data on the aetiology of CH for our patients. Some studies have found no difference in serum T 4 and TSH levels during treatment of CH infants with different aetiologies [8, 14, 15], whereas others found significant differences in the time to TSH suppression in athyrotic infants as compared with infants with ectopic/hypoplastic glands or dyshormonogenesis [20, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…In their cohort, treatment was started later, at a mean age of 45 days, and 47 infants were excluded who failed to meet their stringent inclusion criteria. When hypothyroid infants were treated with a lower T 4 dose (100 µg/m 2 /day, about 6.7 µg/kg/day), only 19% had suppressed TSH levels by 3 months (<6 mU/l) [8]. Abusrewil et al [9], treating infants with a variety of initial doses of T 4 , reported an intermediate number of suppressed cases at corresponding ages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations